Service Providers' Perspectives on Permanent Supportive Housing for Families. Issue 3 (July 2016) - Collins, Cyleste C.; D'Andrea, Rebecca; Dean, Kendra; Crampton, David
This article examines the perspectives and experiences of staff who work for a pilot permanent supportive housing program for families. The program follows Housing First principles by providing supportive housing to chronically homeless families with disabling conditions (typically substance abuse and/or mental health issues). Nine service providers participated in in-depth, semistructured interviews in which they described their experiences with the program, including facilitators and barriers to providing high-quality services for this difficult-to-serve population. The findings indicate that stabilizing families is particularly challenging in part because of the complexity of their needs, both material and instrumental, that are dynamic and ongoing. Implications for practice are discussed, as the Housing First model, established as a best practice for single adults, is applied to families.